How N2 injection improves the hydrocarbon recovery of CO2 HnP: An NMR study on the fluid displacement mechanisms. (15th October 2020) - Dong, Xu; Shen, Luyi W.; Golsanami, Naser; Liu, Xuefeng; Sun, Yuli; Wang, Fei; Shi, Ying; Sun, Jianmeng
Abstract: CO2 HnP, despite its promised potential and societal support for potential carbon negativity, suffered from the elevated cost; its application is limited in scale at the time of this writing. Practitioners had explored a mixture of CO2 with N2 as the treatment gas to reduce the cost and improve recovery. Nevertheless, these efforts are currently thwarted by a lack of understanding of the fluids displacement mechanism on the pore-scale that can only be addressed through laboratory experiments. In this study, we investigate why sequential N2 -CO2 HnP recovers more oil than pure CO2 HnP. We found that N2 and CO2 perform similarly in the displacement of free fluids (FF), but N2 displaces little capillary bound fluids (CAF). However, replacing N2 with CO2 after a few N2 HnP cycles results in significant improvement in the recovery of CAF in the medium-sized pores than the HnP using CO2 exclusively. The injected N2 displaces pore fluids directly by squeezing their volumes but can only work on highly mobile FF. The displacement of fluids by CO2 relies more on creating a fluids/CO2 mixture and the subsequent swelling effect that can also displace CAF. Nevertheless, the N2 does not just 'push' the fluids out but also enhanced the rock's hydraulic conductivity by possibly enlarging the pores and thus resulted in higher CAF recovery in the later cycles of HnP using CO2 . More optimized N2 -CO2 HnP procedures may further boost the recovery of fluids in the medium-sized pores, where a significant amount of hydrocarbon would remain unrecovered.